Investigations on T cell transmigration in a human skin-on-chip (SoC) model. Issue 8 (22nd February 2021) - Ren, Xiaoou; Getschman, Anthony E.; Hwang, Samuel; Volkman, Brian F.; Klonisch, Thomas; Levin, David; Zhao, Min; Santos, Susy; Liu, Song; Cheng, Jasmine; Lin, Francis
Abstract : Our skin-on-chip (SoC) model uniquely enabled quantitative studies of transendothelial and transepithelial migration of human T lymphocytes under mimicked inflammatory skin conditions and was used to test new drug candidates. Abstract : A microfluidics-based three-dimensional skin-on-chip (SoC) model is developed in this study to enable quantitative studies of transendothelial and transepithelial migration of human T lymphocytes in mimicked skin inflammatory microenvironments and to test new drug candidates. The keys results include 1) CCL20-dependent T cell transmigration is significantly inhibited by an engineered CCL20 locked dimer (CCL20LD), supporting the potential immunotherapeutic use of CCL20LD for treating skin diseases such as psoriasis; 2) transepithelial migration of T cells in response to a CXCL12 gradient mimicking T cell egress from the skin is significantly reduced by a sphingosine-1-phosphate (S1P) background, suggesting the role of S1P for T cell retention in inflamed skin tissues; and 3) T cell transmigration is induced by inflammatory cytokine stimulated epithelial cells in the SoC model. Collectively, the developed SoC model recreates a dynamic multi-cellular micro-environment that enables quantitative studies of T cell transmigration at a single cell level in response to physiological cutaneous inflammatory mediators and potential drugs.